Improving Student Entrepreneurship Skills through Training and Mentoring - Ningrum, Tia Ayu; Nurmina, Nurmina; Wildanah, Fifin; Ginanjar, Singgih (Universitas Negeri Padang, 2024)
Every organisation from student organisations, schools and other organisations need training programmes. However, the problem is that there is no training centre that offers the various programmes needed for the development of these student organisations. For this reason, it is necessary to develop a training centre to accommodate the demand for training from student organisations, both university organisations, schools and other student organisations. Furthermore, there is also the problem of the absence of an Entrepreneur Centre that serves to accommodate the results of student entrepreneurship programmes to be sold directly or online. Therefore, it is very necessary and urgent to develop a training centre and entrepreneur centre. So the purpose of this activity is to develop a training centre and entrepreneur center (PEC) Padang through a website platform With this, there is a forum that can accommodate the results of entrepreneurship of Padang State University students and also offer several training programs.The stages that will be carried out are (1) the establishment of a training centre that offers several training programs (leadership, organizational management, proposal making, tutoring etc.) online and offline, (2) mentoring and training student entrepreneurship, (3) creating a website for the Padang training and entrepreneur center (PEC) as a promotional medium. The results of this activity can foster students' entrepreneurial spirit, increase employment opportunities and facilitate student entrepreneurship services and products..